The Self and the Others in About Behaviorism: complications and Implications in a complex culture - Borba, Aécio (Perspectivas em Análise do Comportamento, 2026)
This article discusses the conceptual implications of the chapter “The Self and Others” from B. F. Skinner’s About Behaviorism, offering a critical analysis of how the notion of the “self ” can be understood from a behavior-analytic perspective. The chapter rejects mentalistic and internalist explanations and proposes that the behavior analyst might understand the self as a self-description learned and maintained by a verbal community. Self-knowledge and aspects of self-control are viewed as developments of this idea, explored as socially shaped repertoires in which a person behaves in relation to their behavior. The analysis is further expanded through the contributions of Norbert Elias, particularly regarding the process of individualization in modern market-based societies, which foster predictable behavioral repertoires, emotional control, and an increased need for self-description. The article concludes by highlighting the implications of this approach for the practice of behavior analysts, emphasizing the importance of recognizing the social, political, and ethical dimensions involved in the construction of the self and in the maintenance of repertoires that can either reinforce or challenge oppressive practices in clinical contexts and broader cultural interventions.